“Your Excessive Prophecies Do More Harm than Good.” Wańkowicz on Jewish People - Weiser, Piotr (Porównania, 2025)
This is an attempt to show Melchior Wańkowicz’s opinions on the history and culture of Jews in the context of his activities in interwar Poland and his stay in exile in Mandatory Palestine.